Scholarly communication trends in the digital age: Informal scholarly publishing and dissemination, a grounded theory approach. Issue 6 (2nd November 2015) - Shehata, Ahmed; Ellis, David; Foster, Allen
Abstract : Purpose: – The purpose of this paper is to investigate scholars' attitudes toward informal publishing and dissemination to provide a view of the challenges and advantages of using such channels. Although considerable research has been carried out in relation to peer-reviewed scholarly publishing, relatively few studies have investigated the adoption of informal scholarly communication platforms in the scholarly publishing process. Design/methodology/approach: – The paper deployed a grounded theory approach using semi-structured interviews as a qualitative research tool. A theoretical sample of 40 researchers in 4 universities were interviewed to gather data regarding informal publishing, platforms, factors that affect the researchers' decision and the use of informal channels in dissemination. Findings: – Results of the interviews suggest that there is an increasing trend among researchers toward informal publishing and dissemination throughout the scholarly communication cycle. The paper shows that there are three types of scholars who are involved in the scholarly communication process: conventional, modern and liberal scholars. Each of these scholars carries different beliefs regarding the scholarly communication process. Research limitations/implications: – This paper was conducted on a relatively small sample of academic researchers, and therefore, the results cannot be easily generalized into a wider community of scholars. Originality/value: – The paper provides insight into informal scholarly publishing practices using a grounded theory approach. This approach helped to capture the changes in both scholarly publishing practices and the adoption of informal techniques among the scholarly community.